Park in Baden - Unknown:::Creator::::::::::::; Mollo, Tranquillo, 1767-1837, Wiens Umgebungen:::Contributor:::::::::::: (Tranquillo Mollo; Austria; Vienna)
Color engraving with view of Baden Park in Baden, Austria